The Islamic Economics Studies as the Driving Force of Economic Stability Based on Indonesian Characteristic: Epistemology Perspective - Fauroni, R Lukman (Faculty of Islamic Economics and Business of Institut Agama Islam Negeri (IAIN) Pekalongan, 2019)
This study aims to propose a scientific formula of Islamic economics that can foster growth and contribute to the national economy. This study is the result of research studies reinforced empirical data, using a content analysis with epistemological approaches. The study concluded, in epistemological, Islamic economic sciences can be developed with the inductive model-empirical character in Indonesia and its localities. This Formula has two advantages; First, can parse the economic problems of the nation simultaneously and continuously. Second, the character of Indonesia and its locality to converge with the power of social economic capital owned by the Indonesian nation. With the combination, the implementation of sharia economics can promote economic stability and accelerate the pace of its contribution to the national economy.